The Effect of Birth Ball Therapy on the Intensity of Spontaneous Labor Pain - Setiani, Eka Titi; Latifah, Lutfatul; Anggraeni, Mekar Dwi (Poltekkes Kemenkes Surakarta, 2023)
Background: Labor pain is physiological, with different intensities in each individual, and intermittent. Birth-ball exercises are more comfortable and safer in labor. The birth ball promotes maternal delivery by assisting the mother's posture and assisting the fetus's position to be optimal in order to facilitate the birth process under normal circumstances. This study aimed to define the effect of birth ball therapy on reducing pain intensity in spontaneous labor. Methods: The method of determining the framework uses PICO. Google Scholar, Pubmed, Science Direct, and Sage Journal were used to search for literature. The inclusion criteria were an original experiment study published in English in 2017–2021. The terms